ANALISIS BIOMEKANIKA TANGAN DAN KAKI MANUSIA UNTUK PERANCANGAN ALAT BANTU REHABILITASI PASIEN PASCA-STROKE - , SLAMET WAHYUDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Stroke is the third deadly disease after heart disease and cancer. The rehabilitation program is a form of integrated health services that achieve maximum functional ability and prevent recurrent attacks. Policy rehabilitation at home led to the idea to make an upper-limb and lower-limb post-stroke rehabilitation robotic as a means of therapy post-stroke patients without relying on the therapist. This study aims to determine how much force is required by the upper-limb and lower-limb post-stroke rehabilitation robotic to helps patients undergoing post-stroke therapy. This study begins with designing a seat that serves to measure the performance of human muscles in motion that refers to the practice of physiotherapy stroke motion by Hoeman (1996). The next step is the collection of performance measurement data generated muscle strength of men and women who have had a stroke using the modified seats and digital spring balance. Data collection was performed three times to take the maximum value in each movement followed by biomechanical analysis to calculate the value of the resulting moment. After passing the test of uniformity, adequacy and normality, then find the value of the 5th percentile, 50th percentile, and 95th percentile. The amount of torque used is the moment produced by the 95th percentile in every movement. The final result is moment value of men for elbow internal rotation is 39.86 Nm, shoulder abduction is 51.35 Nm, elbow flexion is 58.17 Nm, shoulder front lateral is 98.78 Nm, leg extention is 148.29 Nm, elbow extention is 60.67 Nm, and leg flexion is 108.24 Nm. And moment value of women for elbow internal rotation is 23.17 Nm, shoulder abduction is 25.74 Nm, elbow flexion is 38.38 Nm, shoulder front lateral is 67.51 Nm, leg extention is 73.12 Nm, elbow extention is 30.71 Nm, and leg flexion is 64.04 Nm.